First-in-Man intrathecal ppplication of neurite growth-promoting anti-Nogo-A antibodies in acute spinal cord injury - Kucher, Klaus; Rupp, Rüdiger; Weidner, Norbert (Neurorehabilitation and neural repair, 2018)
Background. Neutralization of central nervous system neurite growth inhibitory factors, for example, Nogo-A, is a promising approach to improving recovery following spinal cord injury (SCI). In animal SCI models, intrathecal delivery of anti-Nogo-A antibodies promoted regenerative neurite growth and functional recovery. Objective. This first-in-man study assessed the feasibility, safety, tolerability, pharmacokinetics, and preliminary efficacy of the human anti-Nogo-A antibody ATI355 following intrathecal administration in patients with acute, complete traumatic paraplegia and tetraplegia. Methods. Patients (N = 52) started treatment 4 to 60 days postinjury. Four consecutive dose-escalation cohorts received 5 to 30 mg/2.5 mL/day continuous intrathecal ATI355 infusion over 24 hours to 28 days. Following pharmacokinetic evaluation, 2 further cohorts received a bolus regimen (6 intrathecal injections of 22.5 and 45 mg/3 mL, respectively, over 4 weeks). Results. ATI355 was well tolerated up to 1-year follow-up. All patients experienced ≥1 adverse events (AEs). The 581 reported AEs were mostly mild and to be expected following acute SCI. Fifteen patients reported 16 serious AEs, none related to ATI355; one bacterial meningitis case was considered related to intrathecal administration. ATI355 serum levels showed dose-dependency, and intersubject cerebrospinal fluid levels were highly variable after infusion and bolus injection. In 1 paraplegic patient, motor scores improved by 8 points. In tetraplegic patients, mean total motor scores increased, with 3/19 gaining >10 points, and 1/19 27 points at Week 48. Conversion from complete to incomplete SCI occurred in 7/19 patients with tetraplegia. Conclusions. ATI335 was well tolerated in humans; efficacy trials using intrathecal antibody administration may be considered in acute SCI.